Children as Victims in the Social Media: The Islamic Perspective - Shah, HA; Yusof, N; Norfadhilah Mohamad Ali; Abd Shukor, S; Abidah Abdul Ghafar; Ahmad, NM; Musa, NA (American Scientific Publishers, 2024)
Indexed by WOS/ERA